Efecto del peso al destete y a los 18 meses de edad sobre el comportamiento reproductivo futuro de las novillas cebú (2000)
ABSTRACT: Reproductive information of 350 Zebu Bos indicus heifers of a herd located at the Cordoba department's savannas in (Colombia), corresponding to an area of tropical humid forest (bh-T) was analyzed following the procedures GLIII; LSD and retrospective regression of SAS 10, with the objective of evaluating the effect of weaning weight, weight of the heifer at 18 months of age and age and weight at the beginning of mating on their future reproductive behavior. Age and weight at the beggining of mating, service period, pregnancy rate, age at first and second calving, open days and first calcing interval were significantly affected by weight at 18 months of age. Age and weight of heifers at mating, age at first and second calving and open days were predicted via adjusted weaning weight and weight at 18 months of age.